Grammar School Book Collection as a Museum Collection - Lubina, Tihana (Anafora, 2024)
This paper explores and analyses as a museum subject the Grammar School book collection from the Museum of Slavonia, formerly known as the Library of the Royal Grammar School in Osijek. An old book can, due to its historic identity, faithfully reflect the historical events of a certain environment and generate new insights that influenced it through time. In this light, selected units of the Grammar School book collection have been analysed with the aim to show that certain items from the collection can function as museum subjects in the new museum reality. This paper confirms that, through their role as active participants in time and space, such museum subjects can communicate with their unique materials (book bindings, decorations, ex libris, dedications, seals, margin notes, and so on) and become an authentic and reliable historic source for future studies of the cultural and historic uniqueness of the Osijek region.